Membangun Kesadaran Anti Korupsi melalui Pendidikan: Studi atas Bahaya Korupsi bagi Masa Depan Bangsa - Keisya Amanda Lubis; Jihan Jauza Lubis (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Corruption is a serious problem that has widespread impacts on economic, political, social, and moral aspects of society and has the potential to hinder development and threaten the future of a nation. This study aims to analyze the dangers of corruption to the future of the nation and examine the urgency of anti-corruption education as a preventive effort. The research method used is qualitative research with a library research approach, employing descriptive-analytical and normative approaches. The results show that corruption is an extraordinary crime that not only causes financial losses to the state but also damages the character of the younger generation and weakens the system of governance. Anti-corruption education is an effective strategy in building integrity by instilling values such as honesty, responsibility, care, and courage from an early age. In addition, the restorative justice approach in modern legal perspectives supports anticorruption efforts by emphasizing the restoration of social relationships rather than merely focusing on punishment. Therefore, anti-corruption education plays a crucial role as a foundation in creating a generation with strong character and integrity to prevent corrupt behavior and safeguard the future of the nation